Urine Neutrophil Elastase: A Novel Predictor of ICU Admission for Patients with COVID-19 Infection - Song Y; Zeng K; Zhang LK; Zhang JN; Zhang KL; Xin Y; Wang XR; Zhou YX; Li HX; Wang CS; Yu KJ (Journal of Inflammation Research)
Yu Song, Kai Zeng, Li-Kun Zhang, Jian-Nan Zhang, Kai-Li Zhang, Yu Xin, Xin-Ran Wang, Yu-Xin Zhou, Hong-Xu Li, Chang-Song Wang, Kai-Jiang Yu Key Laboratory of Critical Care Medicine of Heilongjiang Province; Department of Critical Care Medicine, The First Affiliated Hospital of Harbin Medical University, Harbin, People’s Republic of ChinaCorrespondence: Chang-Song Wang, Email changsongwang@hrbmu.edu.cn Kai-Jiang Yu, Email drkaijiang@163.comIntroduction: We aimed to explore the differences of neutrophil elastase (NE) levels between intensive care unit (ICU) and non-ICU patients with COVID-19 infection, as well as its predictive value for COVID-19 progression.Methods: We enrolled the patients admitted with a primary diagnosis of COVID-19. All patients in ICU were diagnosed with the critical type upon admission. Blood was taken within 24 hours, followed by examination of the blood NE level and urine NE level. Other clinical features were recorded. A logistic regression model was used to predict ICU admission.Results: A total of 83 patients were diagnosed, including 52 non-ICU cases and 31 ICU cases. The ICU group showed significantly elevated levels of Neutrophil%, Cr, D-dimer (DD), Procalcitonin (PCT), and C-reactive protein (CRP). Meanwhile, the CD3-cell, T4-cell, and Lymphocyte% levels were lower in the ICU group. Notably, the blood NE levels were similar between groups, whereas the urine NE level was highly significantly higher in the ICU group vs the non-ICU group. After dimension reduction, we constructed a logistic model (UD) using only two factors: the urine NE level and the blood DD level. The overall accuracy of was 86.1%. The urine NE has a strong efficacy in ICU prediction (AUC = 0.893), and the performance of the UD model was even better (AUC = 0.933).Conclusion: Urine NE level is a useful predictor of COVID-19 progression, particularly in patients requiring ICU care. Urine NE has a significantly positive correlation with neutrophil%, DD, and PCT, as well as a negative correlation with lymphocyte levels.Keywords: COVID-19, neutrophil elastase, intensive care unit, urine, acute respiratory distress syndrome, ARDS